1983
DOI: 10.1002/star.19830351206
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Glucoamylase on DEAE‐Cellulose

Abstract: The adsorption of glucoamylase on DEAE-cellulose and the properties of the immobilized enzyme in respect to its use in hydrolysis of starch are described.Die Adsorption von Glucoamylase an DEAE-Cellulose. Die Adsorption von Glucoamylase an DEAE-Cellulose und die Eigenschaften des immobilisierten Enzymes hinsichtlich seiner Verwendung bei der Hydrolyse von Starke werden beschrieben.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1986
1986
2013
2013

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Therefore, under the sake bulk conditions (pH 4.0-4.5), cationic adsorbents may be used for adsorption of A. species GA from crude sake materials. It has already been reported that cationic adsorbents, such as DEAE-cellulose, [8] polyethyleneimine-coated Sepabeads, [9] catalytic filamentous carbon coated alumina-selica, [10] and metal-chelated polymer beads [11] were used as an adsorbent for the GA. However, it is expected that these cationic adsorbents having ligands of high pK a cannot selectively remove GA from a GA solution containing organic acids such as lactic acid and acetic acid because they highly adsorb both GA and organic acid.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, under the sake bulk conditions (pH 4.0-4.5), cationic adsorbents may be used for adsorption of A. species GA from crude sake materials. It has already been reported that cationic adsorbents, such as DEAE-cellulose, [8] polyethyleneimine-coated Sepabeads, [9] catalytic filamentous carbon coated alumina-selica, [10] and metal-chelated polymer beads [11] were used as an adsorbent for the GA. However, it is expected that these cationic adsorbents having ligands of high pK a cannot selectively remove GA from a GA solution containing organic acids such as lactic acid and acetic acid because they highly adsorb both GA and organic acid.…”
Section: Introductionmentioning
confidence: 99%